2015
DOI: 10.1101/gad.251520.114
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis TOE proteins convey a photoperiodic signal to antagonize CONSTANS and regulate flowering time

Abstract: Plants flower in an appropriate season to allow sufficient vegetative development and position flower development in favorable environments. In Arabidopsis, CONSTANS (CO) and FLAVIN-BINDING KELCH REPEAT F-BOX1 (FKF1) promote flowering by inducing FLOWER LOCUS T (FT) expression in the long-day afternoon. The CO protein is present in the morning but could not activate FT expression due to unknown negative mechanisms, which prevent premature flowering before the day length reaches a threshold. Here, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(161 citation statements)
references
References 45 publications
5
155
1
Order By: Relevance
“…Finally, in the prr9 mutant where the circadian clock is not strongly affected in light/dark cycles (Appendix Fig S2G; Ito et al , 2003; Farré et al , 2005), HA:CO protein abundance was strongly reduced in the morning when PRR9 is expressed in WT plants (Figs 3I–L and EV3A). Another clock‐controlled gene TOE1 was reported to reduce CO protein abundance under LD (Zhang et al , 2015), and we found that its mRNA levels were increased in toc1 prr5 prr7 prr9 SUC2 :: HA:CO , suggesting that this might contribute to the observed reduction in CO protein abundance (Appendix Fig S2H and I). However, in prr9 SUC2 :: HA:CO where CO protein level is reduced specifically in the morning, TOE1 mRNA level was not increased at this time (Appendix Fig S2H and I).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, in the prr9 mutant where the circadian clock is not strongly affected in light/dark cycles (Appendix Fig S2G; Ito et al , 2003; Farré et al , 2005), HA:CO protein abundance was strongly reduced in the morning when PRR9 is expressed in WT plants (Figs 3I–L and EV3A). Another clock‐controlled gene TOE1 was reported to reduce CO protein abundance under LD (Zhang et al , 2015), and we found that its mRNA levels were increased in toc1 prr5 prr7 prr9 SUC2 :: HA:CO , suggesting that this might contribute to the observed reduction in CO protein abundance (Appendix Fig S2H and I). However, in prr9 SUC2 :: HA:CO where CO protein level is reduced specifically in the morning, TOE1 mRNA level was not increased at this time (Appendix Fig S2H and I).…”
Section: Resultssupporting
confidence: 57%
“…In addition to COP1 and FKF1 that were discussed above, HOS1 and TOE1 have also been implicated in regulating CO stability (Lazaro et al , 2012; Zhang et al , 2015). Although it is possible that HOS1 and TOE1 might also be regulated by PRRs, our genetic data with the cop1 toc1 prr5 prr7 prr9 quintuple mutant do not currently support this hypothesis, because the cop1 mutation is epistatic to the prr mutations with respect to CO protein abundance (Fig 4E and F).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 6B, TOE1 enrichment levels at region C (located in the upstream region of FT) and region R (located in the downstream region of FT) were markedly higher than those at other regions. It was recently shown that TOE1 also associates with the FT promoter at region F and region H ( Figure 6A), which contain AT-rich elements (Dinh et al, 2012;Zhang et al, 2015). In our ChIP-qPCR experiments, however, TOE1 enrichment levels at region F and region H were much lower than those at region C and region R ( Figure 6B).…”
Section: Toe1 Binds the Promoter And Downstream Regulatory Region Ofcontrasting
confidence: 47%
“…These AP2 type proteins are age-dependent regulators of FT, as they are posttranscriptionally regulated by miR172 (Aukerman and Sakai, 2003;Chen, 2004;Song et al, 2013). TOE1 also represses FT expression by physically suppressing the function of CO on the FT promoter (Zhang et al, 2015). TOE1-dependent suppression of FT requires its EAR-like motif, a binding site of TPL.…”
Section: Posttranslational Regulation Of Co Proteinmentioning
confidence: 99%